The psycho-educational counseling training in the practice teaching - Dr. C. Neris Imbert Stable, Dr. C. Neris Imbert Stable; Dr.C. Regla Alicia Sierra Salcedo, Dr.C. Regla Alicia Sierra Salcedo (Transformación, 2021)
Objective: The paper aims at assessing the role of the discipline related to the preservice professional practice of graduates of Psychology and Pedagogy for educational counseling activity.Methods: The authoresses rely on a qualitative methodology based on systematizing the teaching practice by means of a critical review and the searching of alternatives to face problems in counselling training, as well as examining papers registering professor experiences.Results: The authoresses devise a procedure for assessing counseling skill development. Conclusion: The suggested procedure favor students’ efficient performance in psychological pedagogical counseling.
Keywords: Educational counseling; counsellor training; teaching practice; educational planning